2020
DOI: 10.1101/2020.08.13.243303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Furin cleavage of SARS-CoV-2 Spike promotes but is not essential for infection and cell-cell fusion

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infects cells by binding to the host cell receptor Ace2 and undergoing virus-host membrane fusion. Fusion is triggered by the protease TMPRSS2, which processes the viral Spike (S) protein to reveal the fusion peptide. SARS-CoV-2 has evolved a multibasic site at the S1-S2 boundary, which is thought to be cleaved by furin in order to prime S protein for TMPRSS2 processing. Here we show that CRISPR-Cas9 knockout of furin reduces, but does not prevent, t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
147
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(162 citation statements)
references
References 39 publications
15
147
0
Order By: Relevance
“…Whether COVID-19 syncytia arise by the cellular pathways described in this work is unclear, although recent data is supportive. For example, contemporary studies report syncytia in cultured cells following exposure to infectious SARS-CoV-2 (Buchrieser et al, 2020;Cattin-Ortolá et al, 2020;Papa et al, 2020;Xia et al, 2020), an observation that we extend to ACE2/TMPRSS2 A549 cells ( Figure 7F). Further, the synapses that precede fusion (Figure 1) superficially resemble the virus-filled filopodia observed following SARS-CoV-2 infection (Bouhaddou et al, 2020).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Whether COVID-19 syncytia arise by the cellular pathways described in this work is unclear, although recent data is supportive. For example, contemporary studies report syncytia in cultured cells following exposure to infectious SARS-CoV-2 (Buchrieser et al, 2020;Cattin-Ortolá et al, 2020;Papa et al, 2020;Xia et al, 2020), an observation that we extend to ACE2/TMPRSS2 A549 cells ( Figure 7F). Further, the synapses that precede fusion (Figure 1) superficially resemble the virus-filled filopodia observed following SARS-CoV-2 infection (Bouhaddou et al, 2020).…”
Section: Discussionsupporting
confidence: 66%
“…Past studies of respiratory syncytial virus (RSV), human immunodeficiency virus (HIV), and others suggest that cell-cell fusion can play key roles in pathogenicity, whether it be in viral replication, or evasion of the host immune response (Frankel et al, 1996;Johnson et al, 2007;Maudgal and Missotten, 1978). Recent studies on SARS-CoV-2 identified similar syncytia (Buchrieser et al, 2020;Cattin-Ortolá et al, 2020;Ou et al, 2020;Papa et al, 2020;Xia et al, 2020), which may or may not be relevant to patient pathology (Bryce et al, 2020;Giacca et al, 2020;Rockx et al, 2020;Tian et al, 2020). It remains an open question if syncytia are related to viral and host cell membrane composition, and whether their formation provides mechanistic insights into membrane-targeting therapeutics directed toward enveloped viruses including SARS-CoV-2 (Daniels et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous observations (3, 5), we do not detect a neo-N-terminus deriving from the furin cleavage site as the trypsin digestion we employed would not be expected to yield peptides of suitable length for analysis. However, while beneficial for replication, furin cleavage is not essential and other cleavage events within Spike can compensate (15, 16). We detect neo-N-terminal peptides from S637 in both datasets (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such multibasic cleavage sites are not seen in some closely related β‐coronaviruses such as SARS‐CoV 86 although they are present in human coronavirus OC42 (HCoV‐OC43) 92 and human coronavirus HKU1 (HCoV‐HKU1) 93 . The ubiquitous proprotein convertase furin 94 is able to cleave the spike protein of SARS‐CoV‐2 at the S1S2 cleavage site 91,95–97 . Priming of coronavirus spike (S) proteins by host cell proteases is critical for entry of the virus into cells and involves S protein cleavage at the S1/S2 and the S2′ cleavage sites such that the fusion of viral and cellular membranes can occur 91,95–97 .…”
Section: Pathogenesis Of Sars‐cov‐2 Infectionsmentioning
confidence: 99%